Comparative Study of Cryptocurrency Digital Investment Based on Currency Laws and Global Economic Regulations: A Case Study of the Big Four ASEAN Countries - Rico Nur Ilham; Irada Sinta; Fuadi; Arliansyah; Frengki Putra Ramansyah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
e development of cryptocurrency as a digital investment instrument has become a global phenomenon, but its implementation is heavily influenced by domestic regulations and global economic dynamics. This study aims to analyze the influence of clarity in the Currency Law and global economic regulations on cryptocurrency investment, as well as the role of investor confidence as a mediator, through a comparative study of four key ASEAN countries: Indonesia, the Philippines, Singapore, and Thailand. The research method used combines a quantitative approach through analysis of investment and regulatory data, and a qualitative approach through interviews and case studies with investors. The results show that clarity of the Currency Law has a significant influence on investment in Singapore and Indonesia, while global economic regulations are more dominant in the Philippines. Investor confidence has been shown to play a significant role as a mediator, particularly in Singapore and Thailand, in strengthening the relationship between regulation and investment decisions. This research confirms that synergy between domestic and global regulations, as well as investor confidence, is a key factor in maximizing cryptocurrency market growth in ASEAN. These findings provide implications for policymakers to clarify regulations and adopt international standards, and for investors to more comprehensively assess investment risks and opportunities.